Tanggung Jawab Sosial Perusahaan dalam Program Kampanye Sosial - Sulistyaningtyas, Ike Devi (FISIP Universitas Atma Jaya Yogyakarta, 2006)
Abstract:Corporate social responsibility as a paradigm establish and became an importantc roles of business entities. Corporate social responsibility activities is placed and mixing between organization’s goal and social conditions. Attitude of social responsibility have purposes to build the organization’s reputation. Some ways is used to reach attitude of social responsibility, one of them was doing from the social campaigns. Campaign programs agenda is used to empower public as well as organizational member itself.